Strengthening elements to increase fatigue strength of mine hoisting machine steel structures - Mekhtiyev, Ali D.; Kropachev, P. A.; Klyuyeva, Y. G.; Aizhambayeva, S. Zh; Yurchenko, Alexey V.; Alkina, Aliya D. (Metalurgija)
The article deals with the issues of reliable operation of metal structures of mine hoisting machines. A method has been developed that makes it possible to increase the brake device steel beam structures strength, which will further prevent the formation and growth of cracks in the body of the metal structure. It is proposed to strengthen the «weak points» in the structure to increase strength and resistance to fatigue failure with the complete rejection of using expensive high-strength alloys. To study the stress-strain state and fatigue failure of steel structures, the method of computer simulation was used. The article presents the results of studying metal structures of mine hoisting machines by non-destructive testing methods; the percentage of various damages is determined. The article discusses a method for combating fatigue failure of steel structures through the use of elements that strengthen the structure in the places of its fatigue failure.